Peningkatan Keterampilan Teknologi Guru TK Melalui Pelatihan Microsoft Word - Muhammad Fajar Sidiq; Dodi Zulherman; Ipam Fuaddina Adam; Trihastuti Yuniati; Amalia Beladinna Arifa (Edumedia Solution, 2023)
This community service initiative is designed with the primary aim of providing training in the use of Microsoft Word to Kindergarten (TK) teachers in an effort to enhance their technological skills. The workshop aims to offer support to TK teachers in developing their competence in operating this word-processing software, which plays a crucial role in the modern education landscape. The background of this community service initiative reflects the educational transformation that has taken place in recent years. In this digital era, information technology and communication play an increasingly significant role in the learning process. Therefore, TK teachers need to have a strong understanding of relevant digital tools, with Microsoft Word being one of them. This workshop serves as a platform for TK teachers to comprehend and master various features and functions of Microsoft Word, ranging from basic to advanced levels. The importance of this workshop is also reflected in its potential positive impact. With TK teachers becoming more proficient in using Microsoft Word, they will be able to create more engaging, interactive, and relevant learning materials for children in today's digital age. This will enhance the learning experiences of TK students and provide a stronger foundation for their digital literacy development in the future. Furthermore, the workshop creates opportunities for TK teachers to share knowledge and experiences, strengthening collaborative networks among them. By sharing best practices in the use of Microsoft Word, they can support each other in their efforts to improve the quality of early childhood education. The workshop is expected to result in a significant improvement in the technological skills of TK teachers and, in turn, enrich the learning experiences of their students.